Effectiveness of A Fourth Dose of COVID-19 mRNA Vaccine in the Elderly Population During the Omicron BA.2 and BA.5 Circulation: A Nationwide Cohort Study in Korea (K-COVE). (1st March 2023) - Park, Seon Kyeong; Choe, Young June; Jang, Eun Jung; Kim, Ryu Kyung; Lim, Do-Sang; Yi, Seonju; Lee, Sangwon; Kwon, Geun-Yong; Shin, Jee Yeon; Choi, Sang-Yoon; Jeong, Mi Jin; Park, Young-Joon
Abstract: We estimate the effectiveness of a fourth dose booster of coronavirus disease 2019 mRNA vaccine in individuals aged ≥60 years during Omicron BA.2 and BA.5 circulation in Korea. The effectiveness against critical infection was 67.7% (95% confidence interval, 50.7%–78.8%) at 31–60 days and 62.1% (95% confidence interval, 45.5%–73.7%) at 61–90 days. Abstract : Effectiveness of 4th dose booster of COVID-19 mRNA vaccine in Korean adults aged >=60 years during Omicron BA.2 and BA.5 circulation against critical infection was 67.7% (95% CI 50.7%–78.8%) at 31–60 days and 62.1% (45.5%–73.7%) at 61–90 days.